Adenosine receptor A 2b on hematopoietic cells mediates LPS-induced migration of PMNs into the lung interstitium - Konrad, Franziska M.; Witte, Esther; Vollmer, Irene; Stark, Stefanie; Reutershan, Joerg (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2012)
Uncontrolled transmigration of polymorphonuclear leukocytes (PMNs) into the different compartments of the lungs (intravascular, interstitial, alveolar) is a critical event in the early stage of acute lung injury and acute respiratory distress syndrome. Adenosine receptor A 2b is highly expressed in the inflamed lungs and has been suggested to mediate cell trafficking. In a murine model of LPS-induced lung inflammation, we investigated the role of A 2b on migration of PMNs into the different compartments of the lung. In A 2b -/- mice, LPS-induced accumulation of PMNs was significantly higher in the interstitium, but not in the alveolar space. In addition, pulmonary clearance of PMNs was delayed in A 2b -/- mice. Using chimeric mice, we identified A 2b on hematopoietic cells as crucial for PMN migration. A 2b did not affect the release of relevant chemokines into the alveolar space. LPS-induced microvascular permeability was under the control of A 2b on both hematopoietic and nonhematopoietic cells. Activation of A 2b on endothelial cells also reduced formation of LPS-induced stress fibers, highlighting its role for endothelial integrity. A specific A 2b agonist (BAY 60-6583) was effective in decreasing PMN migration into the lung interstitium and microvascular permeability. In addition, in vitro transmigration of human PMNs through a layer of human endothelial or epithelial cells was A 2b dependent. Activation of A 2b on human PMNs reduced oxidative burst activity. Together, our results demonstrate anti-inflammatory effects of A 2b on two major characteristics of acute lung injury, with a distinct role of hematopoietic A 2b for cell trafficking and endothelial A 2b for microvascular permeability. © 2012 the American Physiological Society.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute lung injury; Microvascular permeability; Neutrophils